1987
DOI: 10.1016/s0886-3350(87)80008-1
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy and intraocular lens implantation: A combined procedure

Abstract: We present the results achieved in 26 cases of trabeculectomy combined with intraocular lens implantation after extracapsular surgery in eyes with open-angle glaucoma. Phacoemulsification was performed in nine cases, planned extracapsular cataract extraction in 17. In 23 eyes, a posterior chamber lens was implanted; in three eyes an anterior chamber lens was used because of a ruptured posterior capsule. After a follow-up period ranging from four to 29 months, the postoperative results were satisfactory in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Reports of trabeculectomy alone have achieved an IOP <21 mmHg (with and without treatment) in 85-90% of cases (Watson & Barnett 1975;Wilson 1977;D'Ermo et al 1979;Zaidi 1980;Mills 1981;Watson et al 1990$, although with varying periods of follow-up. Previous reports of combined trabeculectomy and ECCE have achieved an IOP of 21 mmHg or less (again with or without treatment) in between 50-100% of cases with up to 2 years of follow-up (Wilson 1977;Edwards 1980;Mills 1981;Percival 1985;Jay 1985;Galin et al 1985;Skorpik et al 1987;Simmons et al 1987;McCartney et al 1988;Williamson et al 1989). Thus, our results, with all patients achievinganIOP<21 mmHgand89Y00f the standard IOL group and 90% of the heparin-coated IOL group managing this without treatment, are not dissimilar to previous studies of combined trabeculectomy and ECCE.…”
Section: Discussionsupporting
confidence: 67%
“…Reports of trabeculectomy alone have achieved an IOP <21 mmHg (with and without treatment) in 85-90% of cases (Watson & Barnett 1975;Wilson 1977;D'Ermo et al 1979;Zaidi 1980;Mills 1981;Watson et al 1990$, although with varying periods of follow-up. Previous reports of combined trabeculectomy and ECCE have achieved an IOP of 21 mmHg or less (again with or without treatment) in between 50-100% of cases with up to 2 years of follow-up (Wilson 1977;Edwards 1980;Mills 1981;Percival 1985;Jay 1985;Galin et al 1985;Skorpik et al 1987;Simmons et al 1987;McCartney et al 1988;Williamson et al 1989). Thus, our results, with all patients achievinganIOP<21 mmHgand89Y00f the standard IOL group and 90% of the heparin-coated IOL group managing this without treatment, are not dissimilar to previous studies of combined trabeculectomy and ECCE.…”
Section: Discussionsupporting
confidence: 67%
“…In the early 1980s, extracapsular cataract extractions with trabeculectomy were reported to be effective, but larger wound size was associated with more inflammation and hyphaema. [1][2][3] In the 1990s, phacoemulsification and the use of small incision foldable lenses increased the success of combined phacoemulsification/trabeculectomy surgery (phaco/trabeculectomy). Early studies showed promising results.…”
mentioning
confidence: 99%
“…Previous studies reported good results regarding visual acuity and intraocular pressure control when trabeculectomy was combined with ECCE and posterior intraocular lens implantation (PMMA) in patients with coexisting cataract and glaucoma [1][2][3][4]. However, a high prevalence of filtering bleb failure was reported (59% to 78%) [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the astigmatic change following combined ECCE and trabeculectomy was rarely presented and not discussed [1,2,14]. Only Choplin and Monroe [10] dealt with the astigmatism following combined ECCE with trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation